THE EFFECT OF IMPLEMENTING SOCIODRAMA TECHNIQUE GROUP GUIDANCE SERVICES TO IMPROVE THE MORAL OF STUDENTS OF SMP NEGERI 9 MEDAN - Nurhalimah, Nurhalimah; Jamila, Jamila (BRIGHT VISION Journal of Language and Education, 2023)
This research aims to determine the effect of Information Services to Increase the Emotional Intelligence of Class X Students at SMK Tamansiswa Medan for the 2023/2024 Academic Year." This type of research uses quantitative experimental methods, namely one group pretest and posttest design. The subject of this research is class n-k = 23-1= 22 then from the t table we get t = 2.074. Thus tcount>ttable on emotional intelligence is 0.000 <0.05 so that Ho is rejected and Ha is accepted. "It can be concluded that there is an influence of Information Services to Increase the Emotional Intelligence of Class X Students at SMK Tamansiswa Medan.